Short-time work and unemployment in and after the Great Recession - Daniel Kopp; Michael Siegenthaler (ETH Zurich, KOF Swiss Economic Institute, 2019)
Can governmental policies mitigate the effects of recessions on unemployment? We study whether the Swiss short-time work (STW) program reduced unemployment in the 2009-2015 period using quarterly establishment-level panel data linking several administrative data sources. We compare changes in permanent layoffs into unemployment, hiring from unemployment, establishment survival and size between establishments that applied successfully to establishments that applied unsuccessfully for STW at cantonal employment agencies. The latter appear to be a valid control group for the former among others because of substantial idiosyncrasies in cantonal approval practices. We find strong evidence that STW increases establishment survival and prevents rather than postpones dismissals: the 7,880 establishments treated in 2009 would have dismissed approximately 20,500 workers into unemployment (0.46% of the labor force) until 2012. Most workers would have been dismissed in the quarters immediately following application and more than a third would have become long-term unemployed. We estimate that the savings in terms of unemployment benefit payments may have been large enough to compensate the spending on STW benefits for the Swiss unemployment insurance.
Keywords: E24; J23; J63; J65; 330; Great Recession; Labor demand; Layoffs; Labor hoarding; Short-timework; Unemployment; Work sharing